Reconfiguring confined magnetic colloids with tunable fluid transport behavior. Issue 5 (26th December 2020) - Sheng, Zhizhi; Zhang, Mengchuang; Liu, Jing; Malgaretti, Paolo; Li, Jianyu; Wang, Shuli; Lv, Wei; Zhang, Rongrong; Fan, Yi; Zhang, Yunmao; Chen, Xinyu; Hou, Xu
Abstract: Collective dynamics of confined colloids are crucial in diverse scenarios such as self-assembly and phase behavior in materials science, microrobot swarms for drug delivery and microfluidic control. Yet, fine-tuning the dynamics of colloids in microscale confined spaces is still a formidable task due to the complexity of the dynamics of colloidal suspension and to the lack of methodology to probe colloids in confinement. Here, we show that the collective dynamics of confined magnetic colloids can be finely tuned by external magnetic fields. In particular, the mechanical properties of the confined colloidal suspension can be probed in real time and this strategy can be also used to tune microscale fluid transport. Our experimental and theoretical investigations reveal that the collective configuration characterized by the colloidal entropy is controlled by the colloidal concentration, confining ratio and external field strength and direction. Indeed, our results show that mechanical properties of the colloidal suspension as well as the transport of the solvent in microfluidic devices can be controlled upon tuning the entropy of the colloidal suspension. Our approach opens new avenues for the design and application of drug delivery, microfluidic logic, dynamic fluid control, chemical reaction and beyond. Abstract : Collective dynamics of confined magnetic colloids are finely regulated by external magnetic fields, where mechanical properties of colloidal suspension can be probed in real-time, exhibiting tunable microscale fluid transport behavior.